Literary translations foster an educated immigrant community - Pogačar, Timothy (Dve domovini, 2023)
This article examines fiction, and in particular serialized translations, in the Slovenian-American newspaper Prosveta (Enlightenment) during its first decade (1916–1926) and compares it with three Czech-American newspapers in this regard. The comparisons establish—on the background of literary history and journalistic practices—the importance of fiction in immigrant newspapers at that time. The purposes of publishing translations in Prosveta are also considered as they relate to ethnic community building and an extension of nation-building in the United States. The newspaper is viewed as a community-building institution that featured significant reader contributions.
Keywords: 1916-1926; ameriški Slovenci; ethnic community; ethnic newspapers; etnična skupnost; etnični časopisi; književni prevodi; literary translations; Prosveta (časopis); Prosveta (newspaper); Slovenian Americans; Slovenian emigrants; Slovenian literature; slovenska književnost; slovenski izseljenci